Occlusal Changes Following Posterior Tooth Loss in Adults. Part 1: A Study of Clinical Parameters Associated with the Extent and Type of Supraeruption in Unopposed Posterior Teeth - Helen L. Craddock, PhD, M Dent Sci, BDS, MFDS, MRD, FDS (Rest Dent), RCS (Edin), (Journal of Prosthodontics, 2007)
One of the barriers to restoring an edentulous space may be the supraeruption of an unopposed tooth to occupy some or all of the space needed for prosthetic replacement.